2015
DOI: 10.3897/neobiota.25.8613
|View full text |Cite
|
Sign up to set email alerts
|

The thin green line: sustainable bioenergy feedstocks or invaders in waiting

Abstract: Numerous fast growing and highly competitive exotic crops are being selected for production of renewable bioenergy. Tolerance of poor growing conditions with minimal inputs are ideal characteristics for bioenergy feedstocks, but have attracted concern for their potential to become invasive. Miscanthus × giganteus is one of the most promising bioenergy crops in the US, but grower adoption is hindered by high establishment costs due to sterility. Newly developed fertile tetraploid M. × giganteus may streamline c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 58 publications
(73 reference statements)
0
3
0
1
Order By: Relevance
“…A modified version of this general framework has recently been adopted by the UN Convention on Biological Diversity (CBD 2014). Some pathways are increasingly well studied, such as horticulture and forestry as a source for plant invasions (Mack and Erneberg 2002, Dehnen-Schmutz et al 2007a, b, Hanspach et al 2008, Dawson et al 2009, Pyšek et al 2009, Smith et al 2015, Pergl et al 2016a, ballast water transport and aquaculture disseminating aquatic invaders (Galil et al 2009, Mizrahi et al 2015, live plants and plant products introducing pest insects and plant diseases (Roques 2010, Bacon et al 2012, Liebhold et al 2012, Eschen et al 2015a, as well as snails (Bergey et al 2014) and spiders (Nentwig 2015), the aquarium trade (MacedaVeiga et al 2013, Chucholl 2013, tourism (Anderson et al 2015), the pet trade for terrestrial vertebrate invaders (Duncan et al 2003, van Wilgen et al 2010, GarciaDiaz and Cassey 2014, and -more generally -the online trade (Kikillus et al 2012, Humair et al 2015. However, the role of pathways related to unintentional introductions has been difficult to quantify (Lee and Chown 2009, Pyšek et al 2011, Bacon et al 2012.…”
Section: Introductionmentioning
confidence: 99%
“…A modified version of this general framework has recently been adopted by the UN Convention on Biological Diversity (CBD 2014). Some pathways are increasingly well studied, such as horticulture and forestry as a source for plant invasions (Mack and Erneberg 2002, Dehnen-Schmutz et al 2007a, b, Hanspach et al 2008, Dawson et al 2009, Pyšek et al 2009, Smith et al 2015, Pergl et al 2016a, ballast water transport and aquaculture disseminating aquatic invaders (Galil et al 2009, Mizrahi et al 2015, live plants and plant products introducing pest insects and plant diseases (Roques 2010, Bacon et al 2012, Liebhold et al 2012, Eschen et al 2015a, as well as snails (Bergey et al 2014) and spiders (Nentwig 2015), the aquarium trade (MacedaVeiga et al 2013, Chucholl 2013, tourism (Anderson et al 2015), the pet trade for terrestrial vertebrate invaders (Duncan et al 2003, van Wilgen et al 2010, GarciaDiaz and Cassey 2014, and -more generally -the online trade (Kikillus et al 2012, Humair et al 2015. However, the role of pathways related to unintentional introductions has been difficult to quantify (Lee and Chown 2009, Pyšek et al 2011, Bacon et al 2012.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the traits of an ideal biofuel species are the same as those favouring invasiveness (Raghu et al 2006, Buddenhagen et al 2009, Smith et al 2015. Some of the biofuel species (Arundo donax, giant cane; Psidium cattleianum, cattley guava) are even listed among 100 of the worst global invaders of the IUCN (Lowe et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Нещодавно модифікований варіант цієї загальної класифікації був адаптований Конвенцією про біологічне різноманіття (CBD, 2014). Деякі шляхи інвазії патогенів дуже добре досліджені, особливо декоративне садівництво та лісове господарство (Mack, & Erneberg, 2002;Dehnen-Schmutz, Touza, Perrings, & Williamson, 2007a, 2007bHanspach, Kühn, Pyšek, Boos, & Klotz, 2008;Dawson, Burslem, & Hulme, 2009;Pyšek, Křivánek, & Jarošík, 2009;Essl, Dietmar, Dullinger, Mang, & Hulme, 2010;Smith, Allen, & Barney, 2015;Pergl et al, 2016aPergl et al, , 2016b.…”
Section: повернення назад (Spill-back)unclassified